Pengembangan Mi Kering Modifikasi Tepung Ikan Cakalang dengan Tepung Bayam Hijau - Nuryani Nuryani; Regina Ayub; Denny Indra Setiawan; Arifasno Napu; Ayu Bulan Febry K.D (Nutrition Department, Poltekkes Kemenkes Tanjung Karang, 2025)
Noodles are a widely favored food in society. In addition to being affordable and easy to prepare, noodles can serve as an alternative staple food to rice for many Indonesians. Among the many types of noodle products available on the market, dried noodles are particularly competitive and high carbohydrate content. The aimed of study was evaluate the acceptability of noodles modified with skipjack tuna flour and green spinach flour. The method of study was using a completely randomized design (CRD) which was used with four treatments and three replications. Data were collected using an organoleptic test form and analyzed using the Friedman test, followed by the Wilcoxon post-hoc test. Results of study was revealed the most preferred sample in terms of taste was P1 with a score of 3.64. For aroma, P1 was also most preferred with scoring 3.81. The highest preference for color was P1 with scoring 3.98, and for texture, P1 scored the highest at 3.83. The Friedman analysis was indicated the different between four formula in aspect taste, color, aroma, and texture (p = 0,000). The conclusion based on the organoleptic tests, the most accepted formulation in terms of taste, aroma, color, and texture was P1, which contained 5 grams of skipjack tuna flour and 5 grams of green spinach flour. The Mikcabahy product can be use alternative food product high nutrition density.